PENERAPAN SISTEM PAKAR UNTUK DIAGNOSA GIZI BURUK PADA BALITA MENGGUNAKAN METODE FUZZY MAMDANI - Hasanul Fahmi (Jurnal Mantik Penusa, 2017)
Malnutrition is a situation where nutritional intake is very less than the body's needs. Generally poor nutrition is suffered by toddlers because at that age there is a very sharp increase in energy and increased susceptibility to viral or bacterial infections. So that in this study the expert system using fuzzy mamdani method is needed in diagnosing malnutrition in infants. Diagnosis of malnutrition through anthropometric measurement techniques first to determine the nutritional status of children then proceed to the diagnosis stage based on known symptoms so as to produce malnutrition in infants. The application of fuzzy mamdani to determine malnutrition in children under five gets very good results, where the value of the fuzzy mamdani test results reaches 90% truth.Keywords: Malnutrition, expert systems, Fuzzy mamdani, anthropometry